2020
DOI: 10.1002/14651858.cd013432.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Anti-IL-5 therapies for chronic obstructive pulmonary disease

Abstract: Anti-IL5 therapies for chronic obstructive pulmonary disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 32 publications
0
20
0
1
Order By: Relevance
“…Although the meta-analysis on anti-IL-5 in COPD patients already existed ( Donovan et al, 2020 ; Lan et al, 2020 ), study participants were not limited to eosinophilic COPD patients. To provide more accurate and stronger evidence for the efficacy of anti-IL-5 therapy in eosinophilic COPD patients, the current study differs in two ways from the previous meta-analysis ( Dave and Arjun, 2021 ): we only included eosinophilic COPD patients (peripheral blood eosinophil count of 3% or more or >150 cells per cubic millimeter) ( Balkissoon, 2018 ); we compared anti-IL-5 therapy in eosinophilic COPD and in asthma, which enabled a more robust assessment of the effect of anti-IL-5 therapy in eosinophilic COPD patients.…”
Section: Introductionmentioning
confidence: 99%
“…Although the meta-analysis on anti-IL-5 in COPD patients already existed ( Donovan et al, 2020 ; Lan et al, 2020 ), study participants were not limited to eosinophilic COPD patients. To provide more accurate and stronger evidence for the efficacy of anti-IL-5 therapy in eosinophilic COPD patients, the current study differs in two ways from the previous meta-analysis ( Dave and Arjun, 2021 ): we only included eosinophilic COPD patients (peripheral blood eosinophil count of 3% or more or >150 cells per cubic millimeter) ( Balkissoon, 2018 ); we compared anti-IL-5 therapy in eosinophilic COPD and in asthma, which enabled a more robust assessment of the effect of anti-IL-5 therapy in eosinophilic COPD patients.…”
Section: Introductionmentioning
confidence: 99%
“… 84 Cochrane's analysis of anti-IL-5 therapies for COPD has concluded that there was probably little or no difference between the intervention and placebo for quality-of-life measures. 57 Apparently, there is also no major impact of these mAbs on lung function. 85 For other classes of mAbs, information is even more scarce.…”
Section: Discussionmentioning
confidence: 99%
“…A recent Cochrane systematic review that included six studies involving a total of 5542 participants concluded that mepolizumab and benralizumab probably reduce the rate of moderate and severe AECOPDs in the highly selected group of people who have both COPD and higher levels of blood eosinophils (patients with blood eosinophils at the higher end of the normal range as well as those with true blood eosinophilia). 57 …”
Section: Targeting T2-mediated Inflammation Using Mabsmentioning
confidence: 99%
“…More recently, a Cochrane database analysis of 6 studies with 5542 participants who had COPD and were randomized to anti-IL-5 therapy demonstrated that mepolizumab probably reduced the rate of moderate–severe exacerbations in patients with > 150 eosinophils [ 53 ]. In addition, benralizumab reduced the rate of hospitalization in those with an eosinophil count > 220 cells/μl [ 53 ].…”
Section: Introductionmentioning
confidence: 99%